Magnetic Flux Circulation in the Saturnian Magnetosphere as Constrained by Cassini Observations in the Inner Magnetosphere. Issue 11 (3rd November 2021) - Lai, Hairong; Jia, Ying‐Dong; Russell, Christopher T.; Jia, Xianzhe; Masters, Adam; Dougherty, Michele K.; Cui, Jun
Abstract: In steady state, magnetic flux conservation must be maintained in Saturn's magnetosphere. The Enceladus plumes add mass to magnetic flux tubes in the inner magnetosphere, and centrifugal force pulls the mass‐loaded flux tubes outward. Those flux tubes are carried outward to the magnetotail where they deposit their mass and return to the mass loading region. It may take days for the magnetic flux to be carried outward to the tail, but the return of the nearly empty flux tubes can last only several hours, with speeds of inward motion around 200 km/s. Using time sequences of Cassini particle count rate, the difference in curvature drift and gradient drift is accounted for to determine the return speed, age, and starting dipole L‐shell of return flux tubes. Determination of this flux‐return process improves our understanding of the magnetic flux circulation at Saturn and provides insight into how other giant planets remove the mass added by their moons. Key Points: To determine the flux return process, the count rate distributions of ions/electrons inside a flux tube have been studied We use a stretched dipolar magnetosphere model and account for the difference in curvature and gradient drift We estimate the starting dipole L shell of the return flux tubes to be greater than 45